The Expression Of Tragedy In The Poetry Of Abdulhamid Chulpon - Toshpulotova, Gulrukh (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines how tragedy is expressed in the poetry of Abdulhamid Chulpon. Attention is given to pain, loss, silence, broken hope, and the suffering of the homeland. The article studies how tragic meaning is created through tone, symbol, and the relation between personal sorrow and national grief. A close reading method is used together with a brief historical view. The study shows that tragedy in Chulpon’s poetry is not only private sadness. A wider moral and social meaning is also formed. As a result, tragic feeling becomes a poetic form through which the pain of the heart and the pain of the nation are joined in one lyrical space.